Analisis Pengaruh Brand Experience Terhadap Brand Loyalty Dengan Brand Resonance dan Brand Reputation Sebagai Variabel Intervening - Handoko Dwi Wibisono; Imroatul Khasanah (JURNAL STUDI MANAJEMEN ORGANISASI, 2020)
This study aims to determine and analyze the effect of brand experience variables on brand loyalty through brand resonance and brand reputation as an intervening variable for users of the DANA E-Wallet application in Semarang City. The population used in this study are DANA application users who have transacted using the application and are domiciled in the city of Semarang, Central Java. The number of samples used in this study were 100 respondents.In this study, data was collected through distributing questionnaires to selected samples through non-probability sampling techniques with purposive sampling method. Measurement in the questionnaire uses a Likert scale. Five hypotheses were tested using quantitative methods with the data analysis technique used is multiple linear regression which was estimated with the help of computer software in the form of SPSS version 25.The results of the analysis of this study indicate that brand experience has a positive and significant effect on brand resonance, brand experience has a positive and significant effect on brand reputation, brand experience has a positive and significant effect on brand loyalty, brand resonance mediates the effect of brand experience on brand loyalty and brand reputation mediates. the influence of brand experience on brand loyalty.